The teaching learning process of english for specific purposes of students from military colleges - Marrero Hernández, Yanisleydi (Universidad de Ciencias Pedagógicas "Félix Varela Morales", 2012)
This research is placed in the area of knowledge related to English for Specific Purposes in the Teaching-Learning Process in the MININT context at "Luis Felipe Denis Díaz" Military College from Villa Clara, and its fundamental purpose constitutes the satisfaction to the specific needs of communication of the First Year students from Investigation and Criminology profile. During the diagnosis stage different scientific methods were used, so much of the empiric level as of the theoretical level, in order to determine the lacks or inadequacies of this process. A system of actions, based on the theoretical and methodological foundations, in the points of view and definitions endorsed by the authoress of the thesis, and also supported by the results obtained in the diagnosis of necessities was put into practice in a system of classes to achieve a more effective accomplishment of the students of this profile in the interaction with foreigners that use the English language and are involved in a way or another in a criminal situation. Methods like the teacher's diary and the scientific participant observation were implemented in order to reflect, analyze and determine the results of the system of actions proposed. At the same time, a new problem brought out by the research itself was outlined. This system of actions was valued in a satisfactory way, as for its importance and relevance, since it contributed to the formation of the future Investigation Criminologists, capable to face and to solve cases in their professional routine and, at the same time, capable to respond to the interests of the Revolution

La presente investigación se imbrica en el área del saber relacionada con el Inglés con Propósitos Específicos en el ámbito del Proceso de Enseñanza- Aprendizaje en la Facultad Independiente del MININT en Villa Clara "Luis F elipe Denis Díaz", y el propósito fundamental lo constituye la satisfacción a las necesidades específicas de comunicación de los estudiantes de Primer Año del perfil Investigación y Criminalística. Durante la etapa de diagnóstico se utilizaron varios métod os de investigación, tanto del nivel empírico como del nivel teórico, con vistas a determinar las carencias o insuficiencias de dicho proceso. Un sistema de acciones, basado en los fundamentos teóricos y metodológicos, en los puntos de vista y definiciones asumidas por la autora de la tesis, y también por los resultados obtenidos en el diagnóstico de necesidades; fue puesto en práctica en un sistema de clases para lograr un desempeño más efectivo de los estudiantes de esta especialidad a la hora de interactuar con extranjeros que empleen el idioma inglés y estén involucrados de una forma u otra en una situación delictiva. Métodos como el diario de la profesora y la observación científica participante, se implementaron con el propósito de reflexionar, analizar y determinar los resultados del sistema de acciones propuesto. Al mismo tiempo, fue planteado un nuevo problema generado de la propia investigación. Dicho sistema de acciones fue valorado de forma satisfactoria en cuanto a su importancia y pertinencia, ya que contribuyó a la formación de los futuros Investigadores Criminalistas, aptos para enfrentar y resolver casos y situaciones en su desempeño profesional y que a la vez respondan a los intereses de la Revolución
Keywords: Proceso Enseñanza Aprendizaje; Criminalística; Sistema de Acciones; Inglés